Identification of adipose tissue-related predictors of the reduction in cardiovascular risk induced by metabolic surgery - Melchor-López, Alberto; Suárez-Cuenca, Juan Antonio; Banderas-Lares, Diana Zaineff; Peña-Sosa, Gustavo De la; Salamanca-García, Moisés; Vera-Gómez, Eduardo; Hernández-Patricio, Alejandro; Gutiérrez-Buendía, Juan Ariel; Zamora-Alemán, Carlos Ramiro; Alcaráz-Estrada, Sofía Lizeth; Ortiz-Fernández, Moisés; Montoya-Ramírez, Jesús; et al. (Journal of international medical research, 2021)
Objectives We aimed to determine whether parameters associated with adipose tissue (adipocyte density and the circulating concentrations of markers of adipose tissue pathology) predict cardiovascular risk (CVR) modification after metabolic surgery (MS). Methods We performed a case–control study of patients with morbid obesity who were candidates for MS. CVR was defined using flow-mediated dilation (FMD) and carotid intima media thickness (CIMT), which were measured during the 9 months following MS. Subgroups of CVR reduction were defined using the following cut-offs: CIMT 10% and/or a two-fold increase in FMD. Results We studied 40 patients with morbid obesity (mean age 44.5 years, 75% women, mean body mass index 46.4 kg/m2) and high prevalences of the metabolically unhealthy obesity phenotype, hypertension, and diabetes mellitus. A significant reduction in CVR was associated with lower vascular endothelial growth factor-A concentration (6.20 vs. 1.59 pg/mL, respectively), low adipocyte density in visceral adipose tissue (100 vs. 80 cells/field), low infiltration with CD68+ cells (18 vs. 8 cells/field) and higher concentrations of lipid peroxidation markers and malondialdehyde (313.7 vs. 405.7 ng/mL). Conclusion The characteristics of adipose tissue and the circulating concentrations of markers of adipose pathology might represent useful predictors of the reduction in CVR following MS. Clinical trial registration number: NCT0356198 (https://clinicaltrials.gov)